Clinical variants and receptor reflex mechanisms of the cough - V. A. Nikitin; L. V. Vasil’eva (Туберкулез и болезни лёгких)
The paper presents the current data of clinical understanding of the cough based on the analysis of receptor-reflex mechanisms of the cough development. The role of SAR, RAR pulmonary receptors and C-fibers has been investigated as regards the development of the cough. The clinical variants of the cough development both of pulmonary and extrapulmonary nature have been described. The cough is to be managed only after the diagnosis is definite. In the developed countries the accurate diagnostics of the cough nature makes 25%, often the cough can be caused by the two disorders and more. The variants for diagnostic search of the cough cause have been offered in order to optimize the therapy. The treatment of the cough is to be targeted at the suppression of cough or at the easement of expectoration.